The Effect of Head Managerial Leadership on Teacher’s Professionalism - Istaryatinigtias Istaryatinigtias; Rusin Rusin (AT-TA'LIM, 2021)
This study aims to analyze, test research hypotheses, and understand the effect of principal managerial leadership and teacher work discipline on teacher professionalism. Quantitative method was used in this study using a proportional random sampling technique. The total population is 154 teachers from 14 schools. The analysis technique used is descriptive and inferential statistics. The results of the study show that there is a direct positive influence of principals' leadership on teacher professionalism with a correlation coefficient (r13) of 0.891 and a coefficient of determination (r13)2 of 0.7939, as well as the managerial influence of principals. leadership on teacher professionalism with a percentage of 79.39% and a path coefficient (ϸ 31) of 0.072. Second, there is a positive direct influence of teacher work discipline on teacher professionalism with a correlation coefficient (r 23) of 0.830, and a coefficient of determination (r 23) of 0.6889, and teacher work discipline on teacher professionalism with a percentage of 68.89%, and a coefficient of 68.89%. path (ϸ 32) is 0.062. Third, it was also found that the direct positive influence of principal managerial discipline on teacher work discipline with a correlation coefficient (r 12) of 0.831 and a coefficient of determination (21) of 0.6805, as well as the influence of principal managerial leadership. on teacher work discipline with a percentage of 69.05% and a path coefficient (ϸ 21) of 0.831.